Efficacy of Early Yakson Touch and Kinaesthetic Stimulation (Yakin) on the Development of High Risk Neonates: A Randomized Controlled Trial Protocol - Parashar, Preeti; Samuel, Asir John; Aranha, Vencita Priyanka (Journal of Nepal Paediatric Society, 2018)
Introduction: About 15 million babies are born preterm annually, with every year almost 1 million dying from complications and survivors prone to lifetime disability. Yakson touch and kinaesthetic stimulation techniques have proven effective in minimizing the complications and disability of preterm delivery, but presently there is no standardized protocol for their application. The aim is to investigate the efficacy of Yakson touch in combination with kinaesthetic stimulation (YAKIN) on the motor and behavioural development of neonates at high risk of development delay in comparison to conventional handling. Material and Methods: Neonates will be recruited via parental consent from a recognized tertiary care teaching hospital for this two-group pretest-posttest design of randomized controlled trial (RCT), with allocation into either a control group (n=14) or experimental group (n=14) by block randomization method. The experimental group will receive Yakson touch and kinaesthetic stimulation, whilst the control group will receive conventional handling inclusive of developmental positioning and Kangaroo mother care. The duration of intervention will be five out of seven days. Neonatal behavioural assessment scale (NBAS) will be performed at baseline and then on the 7th day to ascertain the intervention effectiveness. Results: Data analysis will be done by Wilcoxon signed rank test/paired t-test and Mann Whitney U test/independent t-test will be done to compare the pre and post intervention score of NBAS within and between groups. The level of significance will be set as p<0.05. Conclusion: The present study may provide valuable information about early intervention to the neonatal physiotherapist, intensivist, nursing staff and parents of neonates.